Cross-shelf distribution of nutrients, plankton, and fish larvae in the San Blas Archipelago, Caribbean Panamá - Luis D'Croz; D. Ross Robertson; José A. Martínez (Revista de Biología Tropical, 1999)
To investigate possible seasonal patterns in water quality and plankton distribution, weekly samples were collected in a coral reef lagoon and in surrounding nearshore waters over a two year period. Additionally, two oceanographic surveys were also conducted in a larger area surrounding the primary study site during the seasonal extremes. The resulting information corroborated previous observations that this area is as an oligotrophic environment. The larger-scale sampling revealed seasonal variation in cross-shelf gradients in plankton, fish-egg and larval densities that are probably related to the strong onshore winds that are typically present during the dry season. Although some limited nutrient enrichment occurs in parts of the nearshore area during the rainy season, the highest plankton density and biomass were recorded in shallow nearshore waters during the windy dry season. Larvae of numerous fish taxa were collected in these nearshore areas during the dry season, suggesting seasonal aggregation. During the rainy season, fish larvae were spread more evenly across the shelf and into nearshelf waters.